Minimally invasive surgical versus catheter ablation for the long-lasting persistent atrial fibrillation. - Jiangang Wang; Yan Li; Jiahai Shi; Jie Han; Chunlei Xu; Changsheng Ma; Xu Meng (PLoS ONE, 2011)
OBJECTIVE: To assess the efficacy of video-assisted minimally invasive surgical vs. catheter ablation for the long-standing persistent AF. METHODS: We performed a retrospective comparative analysis in a series of 166 long-standing persistent AF patients treated between 2006 and 2009 with either video-assisted minimally invasive ablation (83 patients), or catheter ablations (83 patients). The catheter group was screened using a 'pair-matched case-control' methodology in order to select appropriate statistical comparison candidates out of 169 long-standing persistent AF patients which were potentially suitable for surgery, but have been treated with catheter approaches in order to balance major prognostic factors between the two groups. Follow-up for all patients ranged from 1 to 3.6 years. RESULTS: No patient died postoperatively. One patient suffered from stroke in the surgical group but recovered before discharge. Freedom from AF was obtained in 59.0% and 74.7% during follow-up in the catheter group and the surgical group respectively (P = 0.047). Patients in the catheter group had a significantly higher rate of recurrent arrhythmia (P = 0.011, hazard ratio: 0.555, 95% CI: 0.354 to 0.872) compared with the surgically treated group. The freedom from antiarrhythmic drugs was 44.6% in the catheter group and 61.4% in the surgical group (P = 0.043). CONCLUSIONS: The video-assisted minimally invasive ablation was safe and effective, and had an optimistic success rate for patients with long-standing persistent AF in our retrospective comparative study. Thus, further randomized studies addressing this issue seem to be justified.